Stampel Flash Bagi UMKM Percetakan - Zuliyati Zuliyati; Wiwit Agus Triyanto (Universitas Muria Kudus, 2021)
UMKM need to increase their productivity through technology upgrades, so that the production process becomes more effective and efficient. This community service partner is UMKM printing